Canine gastrointestinal stromal tumours treated with surgery and imatinib mesylate: three cases (2018‐2020). (6th November 2022) - Treggiari, E.; Giantin, M.; Ferro, S.; Romanelli, G.
Abstract : Objectives: Gastrointestinal stromal tumours (GISTs) are described in dogs and are histologically diagnosed with the aid of immunohistochemistry to allow differentiation from leiomyomas/leiomyosarcomas. These tumours express c‐kit and in some cases could harbour mutations in KIT coding gene. Materials and Methods: Dogs with a diagnosis of GIST previously confirmed with histopathology and immunohistochemistry were considered for inclusion. Medical records were reviewed for clinical signs at presentation, results of diagnostic tests, tumour location and treatment. To be included, patients had to undergo staging procedures and treatment with imatinib alone or in combination with surgery. Immunohistochemistry and KIT mutational analysis were performed assessing all included cases. Results: Three cases were included. All cases underwent staging procedures and surgical excision. Tumours were located in the stomach (two cases) or caecum (one case). KIT mutational status was assessed and the presence of a 54‐base pair deletion in exon 11 was identified in one case. Following surgery, imatinib was used to treat recurrent, metastatic or residual disease and resulted in complete response and stable disease in the macroscopic setting and no evidence of recurrence in the microscopic setting. Follow‐up time was 890, 120 and 352 days, respectively. Clinical Significance: Surgical and medical treatment resulted in a positive outcome in these cases of canine GIST. Imatinib treatment was well tolerated and resulted in a measurable response and a low spectrum of toxicities. Further studies on the tolerability and efficacy of imatinib in solid tumours and GIST are warranted to define its effectiveness and safety.